Linguistic-Pragmatic Organization of English Language Ecological Internet Discourse - E. B. Pavlova (Научный диалог)
The presents an analysis of linguopragmatics of ecological Internet discourse based on studying the content of English websites of the most well-known international environmental organizations. The relevance of the work is due to the fact that, despite the great interest of scientists to different types and genres of ecological Internet discourse, its linguistic-pragmatic potential as a complex phenomenon has not yet received full scientific coverage. The paper shows that the investigated segment of virtual environmental communication is organized on the basis of a linguistic-pragmatic model, which includes the following components: goal, intention / communicative-pragmatic attitudes, strategies, tactics. This generalized model, revealing the intentions of an addressee, is concretized by the author for the English-language ecological Internet discourse. Particular attention is paid to the main communication strategies of the analyzed discourse, among which there are the strategies of informing, persuasion and evaluation, increasing the activity of an addressee. It is established that these strategies are implemented by information and explaining tactics, tactics of attracting attention, reasoning through an appeal to the facts, authoritative opinion, feelings of an addressee, tactics of positive self-assessment and defamation of the opponent, tactics of inducement, invitation, call, appeal, feedback from an addressee. The author characterizes lexical, lexical-grammatical and linguistic-stylistic means of verbalization of these tactics.